2019
DOI: 10.1177/1744806919882139
|View full text |Cite
|
Sign up to set email alerts
|

Genetic associations of perinatal pain and depression

Abstract: Underlying genetic influences may affect perinatal pain, depression, or both. We investigated the role of 59 single-nucleotide polymorphisms on 20 quantitative traits measured in perinatal women. Moreover, 183 pregnant women (28–37 weeks’ gestation) were prospectively genotyped for single-nucleotide polymorphisms with known prior associations with either pain or depression in nonpregnant populations. Prenatal saliva samples were collected. Phenotypic data were gathered during prenatal, labor and delivery, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…15 A genetic association between labor pain and PPD has also been suggested. Since genetic variants are a common factor between perinatal pain and depression, McClain et al 19 identified genetic loci (C/C genotypes for rs4633) that contribute to PPD and pain in a large cohort of perinatal women. These mapped to genetic regions that may elucidate the mechanisms underlying the relationship between PPD and labor pain.…”
Section: Childbirth Pain and Postpartum Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 A genetic association between labor pain and PPD has also been suggested. Since genetic variants are a common factor between perinatal pain and depression, McClain et al 19 identified genetic loci (C/C genotypes for rs4633) that contribute to PPD and pain in a large cohort of perinatal women. These mapped to genetic regions that may elucidate the mechanisms underlying the relationship between PPD and labor pain.…”
Section: Childbirth Pain and Postpartum Depressionmentioning
confidence: 99%
“…7,8 Causes of PPD are multifactorial, ranging from physiological changes related to pregnancy and childbirth, 9 to psychosocial and environmental factors, including a prior history of mental disorders, low levels of social support, stressful life events and traumatic birth, neonatal intensive care administration, and breastfeeding problems. 10 The spread of the coronavirus disease 2019 (COVID- 19) pandemic across borders has also resulted in extensive fear among pregnant women. Data from the literature indicates that the pandemic has had a significant impact on maternal depression during pregnancy and in the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found a protective relationship between improved pain management and/or labor analgesia and PPD [9–10,11 ▪▪ ,12,13], whereas others have found no relationship [14], or potentially harmful relationships when plans and expectations for labor analgesia utilization do not meet reality [15]. One study found genetic associations between clinical perinatal pain and depression, suggesting a potential biological explanation for these observed relationships between labor pain and depression symptoms [16]. Most observational studies have had limitations including small sample sizes, focus on labor analgesia utilization rather than pain, and incomplete confounding assessment [17 ▪▪ ,18].…”
Section: Labor Pain Analgesia and Depressionmentioning
confidence: 99%
“…Fifty-nine single-nucleotide polymorphisms (SNPs) known to be highly correlative with depressive diagnoses were investigated for their relationships with perinatal pain ratings. Results showed 1 SNP (rs4633, a synonymous SNP in COMT ) to be associated with higher “pain right now” ratings (what is your pain right now) at 6 weeks postpartum and 2 other SNPs (rs1135349, an SNP within a small noncoding RNA that has many previous associations for depression, and rs7548151, intronic in ASTN1 ) to be associated with a higher score for emotional valence of labor pain 50. Ongoing research will continue to identify the molecular basis of both acute pain and PPD.…”
Section: Labor Pain and Analgesia: How Anesthesia May Affect Ppdmentioning
confidence: 99%